Comparative evaluation of the rigidity and accuracy of different elastomeric impression materials with open tray implant level impression technique-An In vitro study - Ashwin N Aidasani; Shailesh Jain; Sahba Hassan; Anu Sharma; C Shanthi; Sandeep Fere (Wolters Kluwer Medknow Publications, 2023)
Introduction: An implant-supported prosthesis requires a precise imprint to provide a good fit. It has been suggested that for implant/abutment level impressions, both the indirect (closed tray) and direct (open tray) methods are effective in achieving a passively fitting prosthesis. Aim: With an open plate embed level impression technique, this in vitro investigation set out to evaluate three different elastomeric imprint materials for their relative rigidity and precision. Materials and Methods: Sixty bespoke trays were created. Part I (rotational opposition assessment) of the investigation included selecting 30 uniquely shaped plates at random and using them to create embed-level open plate engraves. The second part of this investigation (evaluation of rotational discrepancy and vertical inconsistency) used open plate embed level impressions generated with the remaining thirty individualized plates to evaluate how well these materials recreated the patient's impressions. Result: Within the bounds of the current investigation, vinylpolysiloxane had the highest degree of stiffness among the impression materials examined in comparison to polyether and vinylsiloxanether, as seen by its much greater rotational resistance to torquing. A rotational discrepancy was shown to be much lower in polyether open tray implant level impressions compared to vinylpolysiloxane and comparable to vinylsiloxane. Conclusion: In this investigation, the firmest impression medium was vinylpolysiloxane, followed by polyether and vinylsiloxanether for taking imprints of implants. Polyether material, however, was more precise than vinylpolysiloxane and vinylsiloxanether.